2017
DOI: 10.7161/omuanajas.289038
|View full text |Cite
|
Sign up to set email alerts
|

Tuz stresi altindaki biber (Capsicum Annuum L.) bitkisinde bazi organik ve inorganik bileşiklerin antioksidatif sisteme etkileri

Abstract: Laboratuvar şartlarında saksı denemesi şeklinde yürütülmüş olan bu çalışmada, biber (Capsicum annuum L.) bitkisine NaCl (100 mM) yanı sıra, organik bileşiklerden: askorbik asit (0.5 mM), salisilik asit (0.1 mM), nitrik oksit (Sodium nitropruzit; 100 µM), prolin (10 mM) ve inorganik bileşiklerden: silisyum (2 mM), kalsiyum (10 mM) ve potasyum (10 mM) yaprak yoluyla uygulanmıştır. Tuz stresi altındaki biber bitkisinde genel vejetatif gelişme durumu ile bu organik ve inorganik bileşiklerin biber bitkisinin lipit … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…This situation causes Na/K and Na/Ca imbalances in the cell and irregularities in the general ion balance (Chakraborty et al, 2018). Tuna and Eroğlu (2017) reported that NaCl+100 µM SNP they applied to the pepper plant reduced the EC value by around 10% compared with the NaCl application. In our study, the maximum effect of SNP on the improvement of the MP value, which increased approximately three times with the effect of salinity, was determined at 25.0 μM, and it decreased by 32% compared to the NaCl application.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This situation causes Na/K and Na/Ca imbalances in the cell and irregularities in the general ion balance (Chakraborty et al, 2018). Tuna and Eroğlu (2017) reported that NaCl+100 µM SNP they applied to the pepper plant reduced the EC value by around 10% compared with the NaCl application. In our study, the maximum effect of SNP on the improvement of the MP value, which increased approximately three times with the effect of salinity, was determined at 25.0 μM, and it decreased by 32% compared to the NaCl application.…”
Section: Discussionmentioning
confidence: 99%
“…These undesirable adverse conditions are called stress. Stress factors that cause many regressions resulting in low yield in the plant are classified in two ways as abiotic and biotic (Tuna and Eroğlu, 2017). Salt stress, which is one of the abiotic stresses, pollution of groundwater due to natural or artificial events, causes agriculture to be affected by low quality and high salt content irrigation waters.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under stressful conditions, plants synthesize and accumulate organic substances like proline within the cell, which plays a significant role in maintaining membrane integrity and osmotic balance (Tuna & Eroğlu, 2017). Proline amino acid not only contributes to osmotic regulation but also plays a role in adjusting cytosolic pH, preserving the integrity of cellular structures and proteins and activating enzymatic processes under stress conditions (Büyük et al, 2012).…”
Section: Proline Contentmentioning
confidence: 99%
“…Stress factors that cause many regressions resulting in low yield in the plant are classified in two ways as abiotic and biotic (Yildiz et al 2022). Salinity stress, which is the subject of this study, is one of the important abiotic stress factors that limits plant productivity all over the world (Tuna and Eroğlu 2017;Yaman et al 2020). In general, salt damage shows its effect on the form of a smaller structure, a slowdown in growth due to a decrease in the number and area of leaves.…”
Section: Introductionmentioning
confidence: 99%